The Principal's Strategy in Implementing the Kurikulum Merdeka at SMA Negeri 8 Manado - Ayu Lestari; Shelty D.M Sumual; Marthinus Krowin (International Journal Labs, 2023)
This study investigates the management of an Kurikulum Merdeka at SMA Negeri 8 Manado, the principal's strategy, and the results of its implementation. Data was collected through interviews, observations, and documentation, and analyzed using techniques like data reduction, data presentation, and conclusion drawing/verification. Results show that the principal initiates the implementation, receives workshops from the Ministry of Education and Culture and Technology, organizes a learning committee, and implements the curriculum in accordance with government policy. Monthly evaluations and workshops allow for problem-solving and problem-solving. The implementation of the Kurikulum Merdeka has resulted in students developing talents, interests, and abilities, including the P5 project, and improved technology use. Teachers and students have better classroom interactions, freedom of thought, and critical thinking.